Maxillofacial Injury due to Pressure Cooker Explosion in a 13-year-old child: Surpassing The Obvious - Poudel, Kabiraj; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Journal of Nepalese Association of Pediatric Dentistry, 2020)
Pediatric maxillofacial trauma is quiet commonly encountered in the pediatric emergency department. Management of pediatric maxillofacial trauma depends upon the cause and extent of the injury. Maxillofacial trauma due to the explosion of pressure cooker is rare in children. Here, we report a case of pediatric maxillofacial injury due to the explosion of pressure cooker in a domestic setting.